2019
DOI: 10.3389/fpls.2019.01252
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Image-Based Screening Method to Study Water-Deficit Response and Recovery of Barley Populations Using Canopy Dynamics Phenotyping and Simple Metabolite Profiling

Abstract: Plant phenotyping platforms offer automated, fast scoring of traits that simplify the selection of varieties that are more competitive under stress conditions. However, indoor phenotyping methods are frequently based on the analysis of plant growth in individual pots. We present a reproducible indoor phenotyping method for screening young barley populations under water stress conditions and after subsequent rewatering. The method is based on a simple read-out of data using RGB imaging, projected canopy height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Water deficit significantly increased the proline content of all Egyptian barley from to a maximum (54.7 mg FWg -1 ) found in Giza 2000 to minimum (23.1 mg FWg -1 ) under well-irrigated treatment. Similar comments have been reported in many studies of the water stress response of proline accumulation in barley (Mamnouie et al, 2006;Mariey et al, 2017;Saade et al, 2018 ;khatab et al, 2019 andMarchetti et al, 2019), which they reported that the plants had a strategy to cope with water-induced stress is to product and accumulate Free Amino Acids in the cell such as proline content which it act as a compatible solute that adjusts the osmotic potential in the plants under stress.…”
Section: Combined Performance Of Egyptian Barley Cultivarssupporting
confidence: 82%
See 1 more Smart Citation
“…Water deficit significantly increased the proline content of all Egyptian barley from to a maximum (54.7 mg FWg -1 ) found in Giza 2000 to minimum (23.1 mg FWg -1 ) under well-irrigated treatment. Similar comments have been reported in many studies of the water stress response of proline accumulation in barley (Mamnouie et al, 2006;Mariey et al, 2017;Saade et al, 2018 ;khatab et al, 2019 andMarchetti et al, 2019), which they reported that the plants had a strategy to cope with water-induced stress is to product and accumulate Free Amino Acids in the cell such as proline content which it act as a compatible solute that adjusts the osmotic potential in the plants under stress.…”
Section: Combined Performance Of Egyptian Barley Cultivarssupporting
confidence: 82%
“…Regarding total chlorophyll content, in our study we found that water stress had reduced the total Chl content in all cultivars under study. Similar investigations have been studies the response water stress barley such as (Filek et al, 2015;Mariey et al, 2017;Saade et al, 2018;khatab et al, 2019 andMarchetti et al, 2019) which They established that under water stress conditions, barley displays reduced chlorophyll content. However, the mechanisms that confer water stress tolerance and recovery capacity in this crop species are still not fully understood.…”
Section: Combined Performance Of Egyptian Barley Cultivarssupporting
confidence: 68%
“…Chlorophyll fluorescence analysis has been widely used to acquire knowledge about the function of the photosynthetic machinery and for the assessment of photosynthetic tolerance mechanisms to biotic [ 66 , 86 , 101 , 102 ] and abiotic stresses [ 103 , 104 , 105 , 106 , 107 , 108 ], including drought stress [ 21 , 22 , 96 , 108 , 109 , 110 ]. However, DS may not affect a plant leaf uniformly [ 97 ], thus photosynthetic performance may be extremely heterogeneous at the leaf surface, denoting conventional chlorophyll fluorescence measurements non-characteristic of the physiological status of the entire leaf [ 111 , 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll (Chl) fluorescence parameters were recorded using the top‐view FluorCam. A standard protocol was used for the measurement of Chl fluorescence quenching using the Chl fluorescence imaging (CFIM) protocols of the PlantScreen platform as described by Marchetti et al ( 2019 ). Chl fluorescence parameters were calculated using fluorcam 7 (Photon Systems Instruments, https://psi.cz ).…”
Section: Methodsmentioning
confidence: 99%